Virtual Reality: A Possibility for Training Operator 4.0 - Fallaha, Mohamad; Korhan, Orhan; Zeeshan, Qasim (Springer International Publishing Ag, 2022)
At technological advancements have led to the onset of industry 4.0, there must be a shift in the organizational frameworks, wherein manufacturing propensities and the traditional workplaces must transform to adopt a system wherein humans and machines can work together towards a rise in productivity and flexibility. These recent developments call for an up-gradation of the traditional operator to Operator 4.0 or Smart Operator as there has been a rise in a typical, unique work relationships which will require interactions between the operators and machines. These are challenging circumstances for engineers and operators as they must enhance their skills and abilities to keep up with the changing trend. Smart operators will also need to update their cognitive skills parallel with the innovations in the field of virtual reality and wearable technology equipment, as the equipment's augment the abilities of the Operator 4.0. This article aims to (1) Highlight the cognitive ergonomics skills required by operator 4.0 for Virtual Reality VR applications (2) Demonstrate how VR can be used to train future operator 4.0 to do his future tasks (3) Suggest how VR application in manufacturing can be improved for operator 4.0. The methodology in this research involves the usage of Virtual Reality to simulate a factory setup emulating Industry 4.0 factory. Based on the feedback of the participants, the efficiency of VR in training workers in the manufacturing industry can be determined. Also, this exercise can aid designers in avoiding Graphical User Interface issues and further develop the system to maximize efficiency and to provide a positive user experience.
Global Joint Conference on Industrial Engineering and Its Application Areas (GJCIE) -- AUG 14-15, 2020 -- ELECTR NETWORK
Keywords: Industry 4.0; Operator 4.0; Cognitive ergonomics; Virtual reality (VR); Virtual operator; Artificial intelligence (AI); Smart factory